MODEL PENGEMBANGAN KEKHASAN KURIKULUM PROGRAM STUDI PEMASARAN SECARA BERKELANJUTAN DENGAN PENDEKATAN STRUCTURAL EQUATION MODELING - Saptianing, Saptianing; Setiawan, Andi; Astuti, Rif'ah Dwi; Riyanto, Makmun; Wahyuni, Sri (Politeknik Negeri Semarang, 2017)
The process of formulating the curriculum of the Marketing Management Studies Programinvolves the academic community in the Department of Business Administration, industry,professional associations, and alumni. The formulation of the curriculum provides guidance indeveloping an annual activity plan, which contains a series of activities to achieve graduateswho are qualified and able to compete and be able to respond and adapt to environmentalchanges relevant to stakeholder needs and the development of science and technology. Theresults of research course lead to the formulation of a quality curriculum based on the distinctiveadvantages of Marketing Management Program. The sampling technique used in this research isaccidental sampling method in this case is the alumni of Marketing Management study. Thisresearch technique will use two approaches: 1). Confirmatory factor analysis, on StructuralEquation Modeling (SEM); and 2). Regression Weight in Structural Equation Modeling (SEM).The outline of the model in this research can give positive contribution for the curriculum ofMarketing Management Study Program in order to realize the quality of the graduates that theuser wants, either in the form of suggestions of managerial implications, the formulation ofcurriculum development and textbook material. The managerial suggestion is aimed at theCurriculum of Marketing Management Program in formulating the future development programpolicy